LEVERS Learning Framework - Hurley, Mairéad (Trinity College Dublin, 2023)
The LEVERS project (2023-2026) promotes open schooling for innovative science education, with a specific focus on lifelong learning for climate and environmental justice. The project investigates the potential of localised learning ecosystems to support community climate responses in nine countries: Ireland, the UK, Portugal, Belgium, Switzerland, Slovenia, Serbia, Greece, and Cyprus. We are researching the implementation of a transdisciplinary, lifelong- learning approach to science education in these diverse settings across Europe, addressing the complex challenge of the climate and environmental crisis. We believe in partnerships and stakeholder involvement to design meaningful learning and to create a pathway to effective climate responses. We recognise the need for new and different approaches to take action to address local climate issues, while being mindful of inequality, and the social justice aspect of the climate crisis. LEVERS believes in cooperation, learning together and future-making for a just, liveable and sustainable planet. The LEVERS Learning Framework is a foundational document for the LEVERS project, providing the building blocks for the design commitments and pedagogical approaches to be embedded in the learning activities to be undertaken by project partners across Europe. It is Deliverable 1.1 of the LEVERS project. This text aims to be a guide and companion, a source of inspiration and hope for those embarking on journeys that recognise the role that science education has to play in the collective movement towards regenerative, thriving and joyful futures for all terrestrials, human and otherwise.
PUBLISHED
Keywords: Climate change education, sustainability education, STEM education; Inclusive Society; Smart & Sustainable Planet; Sustainability Education; climate change education